Effects of feeding premature infants with Lactobacillus GG on gut fermentation. Issue 5 (November 1993) - Stansbridge, E M; Walker, V; Hall, M A; Smith, S L; Millar, M R; Bacon, C; Chen, S
Abstract : The study aimed to find out whether gut colonisation of premature babies with a probiotic, Lactobacillus GG, modified enteric carbohydrate fermentation. Twenty preterm infants were randomised to receive Lactobacillus GG 10(8) colony forming units twice a day for two weeks or to a control group. Faecal short chain fatty acids (SCFAs), ethanol, and urinary 2, 3-butanediol, were measured in parallel with microbiological studies. Lactobacillus GG colonised nine babies. From 1-28 days of age faecal SCFAs did not differ significantly from controls. Median and ranges were (treated and controls, respectively): acetic acid: 173 (trace-799), 166 (trace-700); propionic acid: 44 (trace-169), 37 (11-229); butyric acid: 31 (5-107), 37 (2-118) mumol/g dry weight. Ethanol was detected in more faecal samples from treated babies (65% v 37%), and at higher concentration (6.3 (trace-40) v 3.3 (0.6-8.8; one 229) mumol/g). 2, 3-Butanediol was found in 66% of urine samples from treated babies and 58% from controls. On 83% of these occasions Klebsiella sp, Enterobacter sp, or Serratia sp were cultured from faeces. Lactobacillus GG had no obvious adverse effects on nutritionally important SCFAs. The small increase in ethanol excretion is unlikely to have clinical significance.